(untitled) (Journal of Contemporary Philology, 2025)
This paper presents the results of an empirical investigation into the typology of indirect causation in English and Macedonian. The study focuses on English causative analytic constructions formed with the verb get and non-finite verb forms. The aim of this research is to identify typological differences in how indirect causation is encoded in the two languages by comparing English constructions with their translational equivalents in Macedonian. Given that English, unlike Macedonian, possesses dedicated lexicogrammatical markers for encoding indirect causation – such as the grammaticalized verb get, we hypothesize that the Macedonian translational equivalents of causative get-constructions will vary depending on the construction type. To test this hypothesis, we extracted examples of these constructions from both fiction and documentary prose. The quantitative analysis of the data shows that the functional equivalents of infinitival contructions are predominantly biclausal structures, whereas the translations of present participial get-constructions tend to use monolexical verbs.